2021
DOI: 10.3389/fcell.2020.624764
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CircNOLC1, Upregulated by NF-KappaB, Promotes the Progression of Prostate Cancer via miR-647/PAQR4 Axis

Abstract: BackgroundCircRNAs recently have shown critical roles in tumor biology. However, their roles in prostate cancer (PCa) remains largely unclear.MethodsCircRNA microarrays were performed in immortal prostate cell line RWPE1 and PCa cell lines as DU145, PC3, LNCaP, C4-2, and 22RV1. Combined with upregulated circRNAs in PCa tissues, circNOLC1 expression was validated in PCa cells and tissues via qRT-PCR and FISH. Sanger sequencing, actinomycin D, gDNA, and cDNA, RNase R assays were used to assess the circular chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…For example, circRGPD6 inhibits cancer stem cell-regulated metastasis of breast cancer by the miR-26b/YAF2 signaling [ 24 ]. Meanwhile, circNOLC1 is enhanced by NF-kB, and induces prostate cancer development by miR-647/PAQR4 axis [ 15 ]. CircNOLC1 enhances progression and tumorigenesis of epithelial ovarian cancer by interacting ESRP1 and regulating RhoA and CDK1 expression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, circRGPD6 inhibits cancer stem cell-regulated metastasis of breast cancer by the miR-26b/YAF2 signaling [ 24 ]. Meanwhile, circNOLC1 is enhanced by NF-kB, and induces prostate cancer development by miR-647/PAQR4 axis [ 15 ]. CircNOLC1 enhances progression and tumorigenesis of epithelial ovarian cancer by interacting ESRP1 and regulating RhoA and CDK1 expression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al reported a circ-ANKS1B highly expressed in BC and closely related to advanced clinical stage and metastasis to lymph node [ 14 ]. CircNOLC1 was recently discovered to be overexpressed in prostate cancer by a microarray analysis, and affect prostate cancer cell proliferation and metastasis [ 15 ]. As critical cancer regulators, miRNAs participate in various biological processes during carcinogenesis via suppressing targeted mRNA translation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, a number of circRNAs have been found to play critical roles in prostate cancer progression. For instance, circRNA nucleolar and coiled-body phosphoprotein 1, circRNA formin 1, circ-0016068, circ_0088233 and circ0005276 are all upregulated in prostate cancer and promote the development of prostate cancer ( Feng et al, 2019 ; Chen et al, 2020 ; Deng et al, 2020 ; Li et al, 2020 ; Shan et al, 2020 ). The findings of the present study extend the current understanding of the function of circRNAs in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Some studies have demonstrated that the expression of circRNAs is markedly dysregulated in tumor samples and widely involved in multiple types of human cancers. [18][19][20] These findings suggested that circRNAs might be an emerging and promising biomarker for the diagnosis and prognostic assessment of malignancies. Recently, a comprehensive microarray and RNA-Seq analysis identified a novel circRNA, has_circ_0000615, which was spliced from the ZNF609 gene, with the length of 874 nt.…”
Section: Introductionmentioning
confidence: 93%